2022
DOI: 10.1007/s12063-022-00283-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of project management on Sustainable Supply Chain development through Industry 4.0 technologies and Circular Economy during the COVID-19 pandemic: A multiple case study of Thai metals industry

Abstract: The COVID-19 pandemic has widely disrupted manufacturing industries. This research focuses on how project management, Industry 4.0 technologies, and the Circular Economy contribute to Sustainable Supply Chain development during the pandemic. A multiple case study focusing on three companies in the metals industry, covering small-, medium-, and large-size companies from Thailand, is adopted to investigate the impact of the pandemic on companies using the dimensions of demand, production, and distribution disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 128 publications
(190 reference statements)
0
6
0
1
Order By: Relevance
“…For example, the efficient use of available resources for maintaining CE is highlighted by Kayikci et al (2021). Similarly, the need for data analytics capability (Kristoffersen et al, 2021), smart and disruptive technologies and feedback systems (Chauhan et al, 2021;Piyathanavong et al, 2022) Sustaining circular economy (Alvarez-Risco et al, 2021), sustainability culture (Zhang et al, 2021a,b), nurture of research culture, continuous improvement of the CE mechanisms (Zanoletti et al, 2021) and ongoing focus for employing cleaner technology (Nandi et al, 2021a, b), to implement and practice CE during a global disruption.…”
Section: Factors That Influence Ce During a Global Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the efficient use of available resources for maintaining CE is highlighted by Kayikci et al (2021). Similarly, the need for data analytics capability (Kristoffersen et al, 2021), smart and disruptive technologies and feedback systems (Chauhan et al, 2021;Piyathanavong et al, 2022) Sustaining circular economy (Alvarez-Risco et al, 2021), sustainability culture (Zhang et al, 2021a,b), nurture of research culture, continuous improvement of the CE mechanisms (Zanoletti et al, 2021) and ongoing focus for employing cleaner technology (Nandi et al, 2021a, b), to implement and practice CE during a global disruption.…”
Section: Factors That Influence Ce During a Global Disruptionmentioning
confidence: 99%
“…(2021). Similarly, the need for data analytics capability (Kristoffersen et al ., 2021), smart and disruptive technologies and feedback systems (Chauhan et al ., 2021; Piyathanavong et al ., 2022) are also considered essential to practice CE during a global disruption. Studies have also mentioned the need for several organizational factors, such as top management commitment (Alvarez-Risco et al ., 2021), sustainability culture (Zhang et al ., 2021a,b), nurture of research culture, continuous improvement of the CE mechanisms (Zanoletti et al ., 2021) and ongoing focus for employing cleaner technology (Nandi et al ., 2021a, b), to implement and practice CE during a global disruption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The pandemic has also expedited the I4.0 technologies and their adaption in promoting sustainable SC development. Piyathanavong et al (2022) have identified the role of I4.0 technologies in promoting SCs during pandemics by conducting a case study on small, medium, and large-scale industries. They have investigated the impact of pandemics on the operations of Thai metals companies.…”
Section: Disruption In Supply Change Due To Pandemicsmentioning
confidence: 99%
“…Motywacja ekonomiczna: integrowanie zrównoważonego rozwoju i zarządzania projektami jako warunek konieczny, by przetrwać na rynku oraz osiągać zyski (Gareis i in., 2011;Herazo i in., 2012;Martens i Carvalho, 2017) Motywacja wizerunkowa: poprawa reputacji, tworzenie pozytywnej narracji (Russell i Shiang, 2012) Motywacja etyczna: budowanie rezyliencji organizacyjnej oraz tworzenie wartości w organizacji (Abidin i Pasquire, 2007), uwrażliwianie na negatywne skutki projektów (Carvalho i Rabechini, 2007) Motywacje strategiczne: projektowanie przewagi konkurencyjnej poprzez dodatkowy impuls do szukania nowatorskich rozwiązań (Gareis i in., 2011), długa perspektywa w myśleniu o rezultatach projektów przekłada się na planowanie strategiczne, uwzględnienie filarów zrównoważonego rozwoju pozwala na lepszą koordynację całych portfoliów (Herazo i in., 2012;Villamil i Hallstedt, 2020) oraz szukanie równowagi między aktualnymi potrzebami a celami strategicznymi (Brook i Pagnanelli, 2014) Zmiana edukacji menedżerskiej (Gaziuluso i Ryan, 2017) i nastawienia menedżerów jako podstawowy fundament wzmacniania zrównoważonego potencjału projektów (Marnewick i in., 2019) Wpływy na ZP Budowanie odpowiedzialnych postaw menedżerów projektów poprzez dążenie do minimalizowania zużycia zasobów (Piyathanavong i in., 2022), ochronę gatunków oraz zasobów naturalnych (Whyte i Mottee, 2022)…”
Section: Argumenty I Konieczne Warunkiunclassified